Adoption Of Web Technologies In The Jordan Education System; A Tool For Educational Development. - Khaled Salem Ali Almahsneh (International Journal of Advanced Science and Technology, 2020)
Web technologies has shown a tremendous improvement in past years, with a significant effect on education causing development of the educational across the globe in several ways. It has also made Jordanian government to formulate policies on IT. Accordingly the study was carried out to assess the adoption of web technologies on educational development with reference to senior secondary schools in Amman. Jordanian government through its policies intends to integrate and streamline the country to the main stream of global IT. The process includes the integration of schools and students to enable them meet the required minimum standard in the IT age. The study inquired about the students‟ knowledge of the web technologies, its usage, and how it affects their academic activities and performance. The study used Primary source of data, while quantitative instrument was used to present and analyses the data. Technological determinism theory was used to guide the study. Among the study findings was that, both urban and rural students are virtually the same in terms of knowledge and usage of web technology, whereby, more than 80% of them have the knowledge and are using it. The study recommends among others that, „A careful plan should be made by the state ministry of education in collaboration with the schools‟ authorities to systematically devise a means of guidance and control of students‟ attitude towards web technologies. This is to make their inclination to it more productive to their academic and attitudinal aspects. This can be done by introducing certain changes and innovations in the schools‟ curriculum that can be attractive and easy to comprehend by the students, that is capable of satisfying their desire for fun and at the same time will enhance their academic capabilities and their mind-set.